The Inferiority Complex of the Muslim Ummah: A Critique of the Islamization of Knowledge in the Era of Globalization - Muhammad Dwi Fajri; Amrin; Amirullah; Zamahsari (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: The dominance of Western civilization in various aspects of life, including politics, economics, and science, has created conditions in which Muslims experience an inferiority complex in the face of modern science. To overcome this, Muslim intellectuals initiated the concept of the Islamization of science as an effort to build a scientific system based on Islamic values. However, this idea has been criticized by several Muslim thinkers who consider that the Islamization of science approach tends to be ideological rather than methodological, and has the potential to create a dichotomy between Islam and global science. Theoretical Framework: The theoretical framework used in this study combines social psychology theories about inferiority complexes and Islamic educational theories that emphasize the importance of building knowledge through Islamic teachings without losing relevance in the global world. Literature Review: The literature reviewed in this study includes various works that discuss the Islamization of knowledge, critiques of the dominance of Western culture, and issues related to globalization and its impact on Muslim identity. Methods: This study uses a qualitative approach with a discourse analysis method to critically examine the various perspectives that have developed regarding the Islamization of science. The data sources used come from literature studies, including the works of Muslim thinkers such as Syed Naquib al-Attas and Ismail Raji' al-Faruqi, as well as criticism from academics who highlight the limitations of this approach. Results: The results of the study show that although the Islamization of science attempts to restore the intellectual superiority of Muslims, this approach faces serious challenges, such as the lack of a transparent methodology, limited implementation in higher education, and the possibility of academic isolation from the global scientific community. Implications: Therefore, this study offers an alternative, more integrative approach, namely the reconstruction of the Islamic scientific paradigm that not only maintains Islamic values but can contribute to universal scientific discourse without getting caught up in the Islam vs West dichotomy. Novelty: This study presents a novel critique of the Islamization of knowledge by addressing the inferiority complex among Muslims in the face of Western scientific dominance. Unlike prior ideological approaches, it proposes a methodological reconstruction of the Islamic scientific paradigm that integrates Islamic values with global discourse, avoiding the Islam-versus-West dichotomy.